Niclosamide Analogs for Treatment of Ovarian Cancer. Issue 8 (October 2015) - Walters Haygood, Christen L.; Arend, Rebecca C.; Gangrade, Abhishek; Chettiar, Somsundaram; Regan, Nicholas; Hassmann, Christopher J.; Li, Pui-Kai; Hidalgo, Bertha; Straughn, John Michael; Buchsbaum, Donald J.
<x xml:space="preserve">Abstract</x> Objective Niclosamide has shown activity against ovarian cancer in vitro; however, it has low bioavailability in vivo. Therefore, we investigated the cytotoxicity of niclosamide analogs in combination with carboplatin against ovarian cancer patient ascites cells and tissue slices. Materials/Methods Tumorspheres were isolated from ascites collected from patients undergoing ovarian cancer surgery and plated at 10, 000 cells per 50 μL into low attachment plates. Tumor slices were also processed at the time of surgery. These were treated concurrently with niclosamide or analogs (0.1–5 μM) and carboplatin (5–150 μM). At 48 hours, cell viability was assessed with ATPlite assay. Western blotting was used to determine expression of Wnt/β-catenin proteins in ascites cells. Results Cytotoxicity of niclosamide and its analogs in combination with carboplatin was demonstrated in 24 patient ascites samples. Increased cytotoxicity was seen with 2 analogs in 23 patient ascites samples when compared with niclosamide. Similar cytotoxicity was produced in an ex vivo tumor slice model. Western blot analysis showed decreased expression of Wnt/β-catenin proteins with niclosamide and analog treatment in a dose-dependent fashion. Conclusions The niclosamide-like analogs produced cytotoxicity both alone and in combination with carboplatin against tumorspheres from patient ascites and slices from solid tumor samples. Tumor slices showed similar cytotoxicity to matched ascites samples. Western blots showed down-regulation of Wnt pathway–associated proteins in patient samples treated with niclosamide analogs. These results suggest that more soluble niclosamide analogs may be useful for the treatment of ovarian cancer in combination with chemotherapy.